2015
DOI: 10.1002/jhm.2489
|View full text |Cite
|
Sign up to set email alerts
|

SOAP‐V: Introducing a method to empower medical students to be change agents in bending the cost curve

Abstract: Medical students must learn how to practice high‐value, cost‐conscious care. By modifying the traditional SOAP (Subjective‐Objective‐Assessment‐Plan) presentation to include a discussion of value (SOAP‐V), we developed a cognitive forcing function designed to promote discussion of high‐value, cost‐conscious care during patient delivery. The SOAP‐V model prompts the student to consider (1) the evidence that supports a test or treatment, (2) the patient's preferences and values, and (3) the financial cost of a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…22 A recent study on the effect of a value-added presentation format for medical students showed this concept can apply to medical students and improve their comfort in considering value in decisionmaking. 23 However, the presence of a formal curriculum in the absence of faculty role modeling is likely insufficient for training, as demonstrated by the fact that Institution 1 had a formal HVCCC curriculum but residents were still dissatisfied. The ideal curriculum desired by residents also strongly prioritized informal discussion on rounds, which further supports that the presence of a formal curriculum alone is not sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…22 A recent study on the effect of a value-added presentation format for medical students showed this concept can apply to medical students and improve their comfort in considering value in decisionmaking. 23 However, the presence of a formal curriculum in the absence of faculty role modeling is likely insufficient for training, as demonstrated by the fact that Institution 1 had a formal HVCCC curriculum but residents were still dissatisfied. The ideal curriculum desired by residents also strongly prioritized informal discussion on rounds, which further supports that the presence of a formal curriculum alone is not sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…When formulating diagnostic impressions and management plans, conscious consideration should be given to adding a value statement detailing the perceived benefits, harms and costs of what is being planned. 31 Focused attention on the consequences of decisions may reframe any negative connotations of not doing certain things to a positive stance of configuring care to bestow the highest value for that patient. Any potential for omission regret felt by the clinician may be reframed as offsetting patient regret from their consenting to a management plan that results in undesired outcomes.…”
Section: Value Of Care Considerations In Clinical Assessmentsmentioning
confidence: 99%
“…Some schools have begun training students to write SOAP-V notes on their patients, where the "V" stands for "value." [15] In these notes, the student comments on the effectiveness of the plan as it pertains to cost of the plan, effectiveness of the plan, and also possible better viable alternatives (suggested by the literature or otherwise). In this way, the student is more an active participant in review of the patient care the team delivers.…”
Section: High Value Care Curriculummentioning
confidence: 99%